Choice of drugs in the treatment of chronic hepatitis B in pregnancy - Guclu, Ertugrul (Baishideng Publishing Group Co., Limited, 2013)
The selection of antiviral drugs for chronic hepatitis B (CHB) treatment in pregnancy is very difficult since none of the drugs have been approved for use in pregnancy. Transmission from mother to newborn remains the most frequent route of infection in mothers with high viral load and positive hepatitis B e antigen status, even with the use of appropriate prophylaxis with hepatitis B virus (HBV) immunoglobulin and HBV vaccination. We read from the article written by Yi et al that lamivudine treatment in early pregnancy was safe and effective. However, we could not understand why adefovir dipivoxil (ADV) was used in three pregnancy cases, since ADV has been classified as pregnancy category C. In pregnancy, telbivudine or tenofovir should be selected when the treatment of CHB is necessary, since these drugs have been classified as Food and Drug Administration pregnancy risk category B.